Conservation implications of Rainbow trout (Oncorhynchus mykiss) invasions in the upper Blyde River system, South Africa - Zengeya, Tsungai A. (University of Pretoria, 2023)
Thesis (PhD (Zoology))--University of Pretoria, 2022.